New Steroid–Alkaloid Bioconjugates as Potential Bioactive Compounds: Synthesis, Spectroscopic and In Silico Study - Hanna Koenig; Karolina Babijczuk; Kamil Ostrowski; Damian Nowak; Tomasz Pospieszny; Beata Jasiewicz (Applied Sciences)
The search for new biologically active compounds with prospective pharmaceutical applications has motivated the investigation of alternative synthesis pathways. One such approach involves the development of compounds with established biological activity as lead compounds. The focus on compounds of natural origin is gaining prominence, with steroids and alkaloids representing notable examples. Our research aimed to synthesize novel steroid–alkaloid bioconjugates with potential biological activity. The structure of all new compounds was determined using spectroscopic methods. The final heats of formation (HOF) for all bioconjugates were also calculated. In silico methods demonstrated that most obtained compounds, especially caffeine derivatives, exhibited potential biological activity. These compounds act as cholesterol antagonists, analeptics, antihypercholesterolemic, and respiratory analeptic compounds. The molecular docking results for the 1HWK and 6RZ4 protein domains indicate that the selected bioconjugates exhibit affinities comparable to or lower than those of atorvastatin (−9.6 kcal/mol), the reference ligand in cholesterol-lowering. Conversely, the affinities of the selected bioconjugates are higher than those of caffeine (−6.2 kcal/mol), which is used as the reference ligand for analeptic drugs.